2000
DOI: 10.1073/pnas.011384898
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of opioid receptors with beta 2-adrenergic receptors: A role in trafficking and mitogen-activated protein kinase activation

Abstract: G-protein-coupled receptors (GPCRs) have recently joined the list of cell surface receptors that dimerize. Dimerization has been shown to alter the ligand-binding, signaling, and trafficking properties of these receptors. Recent studies have shown that GPCRs heterodimerize with closely related members, resulting in the modulation of their function. In this study, we have attempted to determine whether members of GPCR superfamilies that couple to different families of G-proteins can associate and form oligomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
156
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 32 publications
7
156
1
3
Order By: Relevance
“…The previous blockade of A 1 R or A 2A R prevents the internalization mediated by both A 1 R and A 2A R agonists, suggesting that internalization of heteromer in response to agonists is a consequence of heteromer overactivity. Confocal imaging of transfected HEK-293T cells confirmed that exposure to an A 1 R agonist led to internalization of not only A 1 R but also A 2A R and, conversely, exposure to an A 2A R agonist led to internalization of not only A 2A R but also A 1 R. Thus, in this aspect, A 1 -A 2A R heteromers behaved as the β2-adrenoceptor-δ-opioid [31] and μ-opioid-tachykinin NK1 [32] receptor heteromers but different from other heteromers whose protomers do not co-internalize [see 33]. It is technically difficult to know to what extent adenosine receptor internalization affects GABA transport in astrocytes.…”
Section: Discussionmentioning
confidence: 81%
“…The previous blockade of A 1 R or A 2A R prevents the internalization mediated by both A 1 R and A 2A R agonists, suggesting that internalization of heteromer in response to agonists is a consequence of heteromer overactivity. Confocal imaging of transfected HEK-293T cells confirmed that exposure to an A 1 R agonist led to internalization of not only A 1 R but also A 2A R and, conversely, exposure to an A 2A R agonist led to internalization of not only A 2A R but also A 1 R. Thus, in this aspect, A 1 -A 2A R heteromers behaved as the β2-adrenoceptor-δ-opioid [31] and μ-opioid-tachykinin NK1 [32] receptor heteromers but different from other heteromers whose protomers do not co-internalize [see 33]. It is technically difficult to know to what extent adenosine receptor internalization affects GABA transport in astrocytes.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast to the effects of Mas, Ang II mobilization of [Ca 2ϩ ] i was unaffected by the presence of the G q/11 -coupled sphingosine-1-phosphate [S1P 3 ], urotensin II, or muscarinic M 3 acetylcholine receptors (Figure 2 23 The differential effects on AT 1 -mediated Ang II binding capacity on the one hand and signaling on the other by the coexpression of Mas suggested that the AT 1 receptor was physically altered by Mas such that the enhanced cell-surface expression of the AT 1 receptor was offset by reduced receptor functionality, most likely due to a conformational constraint on AT 1 signaling within the hetero-oligomer. The potential for such direct interactions between Mas and the AT 1 receptor was thus investigated with various forms of BRET.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, different receptors coexpressed in the same cell present certain promiscuity to heterodimerize (Jordan et al, 2001;McVey et al, 2001;Pfeiffer et al, 2002;Salim et al, 2002).…”
Section: Gpcr Heterodimerization: a Source Of Functional Diversificationmentioning
confidence: 99%